The Effect of Training and Development on Employee Retention with Job Satisfaction as an Intervening Variable on Members of The East Java Regional Police Ditreskrimum (Maneggio, 2025)
This study aims to analyze the effect of training and development on employee retention with job satisfaction as an intervening variable on members of the Ditreskrimum Polda Jatim. This study uses a quantitative approach with the Partial Least Square (PLS) method to test the relationship between variables. The research sample consisted of 43 members of the Ditreskrimum Polda Jatim who were selected using purposive sampling techniques. The results of the study indicate that training has a significant positive effect on job satisfaction and employee retention. However, development does not have a significant effect on job satisfaction or employee retention. In addition, job satisfaction also does not have a significant effect on employee retention. However, when training, development, and job satisfaction are combined, all three overall have a significant effect on employee retention. This study concludes that relevant and effective training is a key factor in increasing job satisfaction and member retention. However, development programs need to be evaluated to be more relevant to member needs. The Ditreskrimum Polda Jatim is advised to improve training and development programs, as well as pay attention to other factors such as compensation, work environment, and work-life balance to increase overall member retention.